Culinary MSME Purchase Decisions Under Food Price Pressure in the MBG Era - Elizabeth Haloho; Ronnie Togar Mulia Sirait (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines factors shaping culinary MSME consumers’ purchase decisions under food price pressure in the MBG era. Design/methodology/approach – A quantitative exploratory-confirmatory survey design was used. Data were collected in two stages, involving 203 valid responses for EFA and 228 valid responses for CFA. Reliability and validity were assessed using Cronbach’s Alpha, CR, AVE, and model fit indices. Findings/Results – EFA identified six factors: perceived price fairness, perceived value, product quality, consumer trust, pricing strategy adaptation, and purchase commitment. CFA confirmed that the six-factor model met acceptable loading, model fit, reliability, and convergent validity criteria. Originality/Value – This study positions culinary MSME purchase decisions under food price pressure as multidimensional evaluations, highlighting pricing strategy adaptation as a consumer-evaluated dimension.